PELATIHAN APLIKASI “KAHOOT” SEBAGAI MEDIA DALAM PROSES DAN EVALUASI PEMBELAJARAN BAGI PARA GURU BAHASA JERMAN DI SMA NEGERI 6 AMBON - Patresia S Apituley; Grietje H Kunu; Eldaa Crystle Wenno; Piet Soumokil (German für Gesellschaft (J-Gefüge), 2023)
The use of educational game-based media in general has not been implemented in schools in Ambon city. Even though in the digital era 4.0 educators are required to be able to use educational game-based media in the teaching and learning process. Therefore, it is necessary to provide German teachers in Ambon City at the SMA / SMK level with training on the use of technology in the learning process, one of which is the "Kahoot" Application Training as Media in Learning Process and Evaluation for German Language Teachers at SMA Negeri 6 Ambon. The community service team carries out training activities with the aim of training the use of educational game-based media in the learning process and evaluation. Community service activities are carried out through demonstration methods and direct practice in making learning media using the kahoot application. This activity was attended by German teachers in Ambon City. The end result of this service activity is the production of an educational game-based media (Kahoot) in the learning process and evaluation. This media can be used as an alternative in improving the skills of teachers in the process and evaluation of learning